Aeshna shennong sp. nov., a new species from Hubei Province, China (Odonata: Anisoptera: Aeshnidae) - Zhang, Hao-Miao; Cai, Qing-Hua (Zootaxa, 2014)
Aeshna shennnong sp. nov. (holotype male: Dajiuhu national wetland park in Shennongjia National Nature Reserve, Shennongjia City, Hubei Province, China, 28. VIII. 2013) is described, illustrated and compared with its most similar congener, A. petalura Martin, 1908. The holotype will be deposited in the Collection of Aquatic Animals, Institute of Hydrobiology, Chinese Academy of Sciences, Wuhan City, Hubei Province, China. New distribution records of A. petalura from mainland China are also provided.